Meeting of Deputy Ministers Copenhagen, Denmark. May 27, 2010. Statement by Denmark. - Ministry of Foreign Affairs of Denmark (2010)
Danish statement at the first Deputy Ministers' Meeting of the Arctic Council held in Copenhagen, Denmark 27 May 2010.